The First Molecular Characterization of Baltistan or Karakorum Gecko, Altiphylax stoliczkai (Steindachner, 1867) from Leh, Ladakh, India - Archana, Bahuguna (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The distribution of saurian species in Ladakh is less documented compared to mammals and birds. Additionally, there are very few molecular studies on the lizard species inhabiting the high altitudes of this region. In this study, we collected two road-killed specimens of Altiphylax stoliczkai (Steindachner, 1867), commonly known as the Baltistan gecko or Karakorum gecko, from Ganglaas, Leh, Ladakh. This locality is newly recorded for the species. We conducted a molecular analysis based on the COX1 gene to differentiate between Altiphylax stoliczkai and Altiphylax tokobajevi (Jeremcenko & Szczerbak, 1984). This research represents the first molecular analysis of Altiphylax stoliczkai from Leh, Ladakh, India.